2005
DOI: 10.1007/s10661-005-8043-6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Organochlorine Pesticide Residues in Summer and Winter Vegetables from Agra, India – A case study

Abstract: Analysis of summer and winter vegetable samples during 2002-2003 for pesticidal contamination was carried out on Gas Chromatograph-Electron Capture Detector with capillary columns. The contamination levels of winter vegetables (average concentration of 4.57, 6.80 and 5.47 ppb respectively for Lindane, Endosulphan and DDT) were found to be slightly higher than the summer vegetables (average concentration of 4.47, 3.14 and 2.82 ppb respectively for Lindane, Endosulphan and DDT). The concentration of these organo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 7 publications
2
19
2
Order By: Relevance
“…This result may be due to the variation in the nature and quantity of spraying pesticides from place to place. Most reports concerning only organochlorine pesticide analysis in vegetable and fruits samples are reported from India (Bhanti et al, 2004;Bhanti & Taneja 2005;Kumari, Kumar & Kathpal 2001;Mandal & Singh 2010;Sharma et al, 2010). The levels of pesticides found in this study were lower than previously reported levels in vegetables (5e12350 ng g À1 ) in India (Srivastava et al, 2011) and higher than in other countries like Hungary (10 ng g À1 ) (Kmeller, Abranko, Fodor & Lehotay 2010).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This result may be due to the variation in the nature and quantity of spraying pesticides from place to place. Most reports concerning only organochlorine pesticide analysis in vegetable and fruits samples are reported from India (Bhanti et al, 2004;Bhanti & Taneja 2005;Kumari, Kumar & Kathpal 2001;Mandal & Singh 2010;Sharma et al, 2010). The levels of pesticides found in this study were lower than previously reported levels in vegetables (5e12350 ng g À1 ) in India (Srivastava et al, 2011) and higher than in other countries like Hungary (10 ng g À1 ) (Kmeller, Abranko, Fodor & Lehotay 2010).…”
Section: Discussioncontrasting
confidence: 58%
“…In India most report concerning on organochlorine pesticide analysis in food samples (Bhanti, Shukla & Taneja 2004;Bhanti & Taneja 2005;Kumari, Kumar & Kathpal 2001;Mandal & Singh 2010;Sharma, Nagpal, Pakade & Katnoria 2010) and few studies have been reported on the measurement of OP pesticides in food samples (Srivastava, Trivedi, Srivastava, Lohani, & Srivastava, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The residue levels from Accra markets are comparable to those found in vegetables from Gambia and Senegal as well as vegetables from Deyang and Yanting Areas of the Chengdu Economic Region, Sichuan Province, China (Manirakiza et al, 2003 andOwago, Qi, Xinli, Yuan, &Muhayimana, 2009) but lower than those found in Agra, India (Bhanti & Taneja, 2005), Debrecen, Hungary (Hovánski et al, 2007), Shanghai, China (Nakata et al, 2002) and Nigerian markets (Adeyeye & Osibanjo, 1999).…”
Section: Pesticidesmentioning
confidence: 51%
“…The presence of pesticide residues in vegetables has become a global phenomenon. Authors have reported the residues of OCs, OPs and SPs, along with fungicide and herbicides in fruit and vegetables from India (Dikshit et al 1990;Kumari et al 2002Kumari et al , 2003aKumari et al , b, 2006Shahi et al 2005;Bhanti and Taneja 2005) and abroad (Frank et al 1987;Wang et al 2008;Quintero et al 2008). Further, the persistence and half-life period of many pesticides were found to be less in tropical countries (Rup et al 1989).…”
Section: Resultsmentioning
confidence: 99%